Analisis Pengaruh Gaya Kepemimpinan, Budaya Kerja, Dan Beban Kerja Terhadap Kinerja Karyawan PT GMF Aeroasia Tbk - Ricko Raharjo; Andriansyah Bachtillah Putra (Jurnal Manajemen Bisnis Era Digital, 2024)
This aims to analyze the influence of leadership, work culture and workload on employee performance at PT GMF Aeroasia Tbk. The population in this study were employees who worked in Hangar 3 Unit PT GMF Aeroasia Tbk as many as 320 employees, this study used the Proportional Sampling Sampling technique. Methods of data collection using survey methods, with the research instrument is a questionnaire. The data analysis method uses IBM SPSS Statistics 22. This study proves that leadership style has a positive and significant effect on employee performance. Work culture has a positive and significant effect on employee performance. Workload has a positive and significant effect on employee performance.